2019
DOI: 10.1002/iub.2012
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MEG3 suppresses migration and promotes apoptosis by sponging miR‐548d‐3p to modulate JAK–STAT pathway in oral squamous cell carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is a lethal malignancy and its prognosis remains dismal. Thus, a deeper understanding of the mechanisms is needed to provide a new insight for new therapies. It has been reported that long noncoding RNA (lncRNA) maternally expressed gene 3 (MEG3) was downregulated in OSCC tissues, however, its functional mechanism remains uncertain. Here, we found that the overexpression of MEG3 suppressed migration and promoted apoptosis in OSCC cell lines, while inhibition of MEG3 exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 32 publications
6
39
0
Order By: Relevance
“…Recently, the important roles of lncRNAs have been widely investigated in the progression of OSCC. Previous studies have indicated shown that lncRNA can play an inhibitory or carcinogenic effect in OSCC (20,21). In this study, upregulation of lncRNA SNHG5 was detected in OSCC.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, the important roles of lncRNAs have been widely investigated in the progression of OSCC. Previous studies have indicated shown that lncRNA can play an inhibitory or carcinogenic effect in OSCC (20,21). In this study, upregulation of lncRNA SNHG5 was detected in OSCC.…”
Section: Discussionsupporting
confidence: 52%
“…MEG3 has been proposed to play a biological role in various diseases, particularly cancer. Recent studies demonstrated that MEG3 is involved in the regulation of cancer-related pathways, and contributes to cell proliferation, metabolism, tumor progression and metastasis (9)(10)(11)(12)(13)(14). In the present study, the expression and role of MEG3 in ESCC were assessed, and the mechanisms underlying its activity were investigated.…”
Section: Discussionmentioning
confidence: 92%
“…The lncRNA maternally expressed gene 3 (MEG3) is widely expressed in a variety of normal tissues. MEG3 has been identified as a tumor suppressor and is expressed at lower levels in diverse types of cancer (9)(10)(11)(12)(13). However, whether MEG3 is involved in the EMT process of ESCC remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that lncRNA plays a critical role in the initiation, development, and progression of human cancer by functioning as an endogenous microRNA (miRNA) sponge . For example, LINC00336 was reported to facilitate lung cancer progression via sponging miR‐6,852; LncRNA SNHG6 directly bound to miR‐26a/b and miR‐214 to promote the growth and metastasis of colorectal cancer; LncRNA MEG3 was proposed to suppress migration and promote apoptosis of oral squamous cell carcinoma cells by effectively sponging miR‐548d‐3p . Likewise, several lncRNAs have also been identified to be involved in ESCC tumorigenesis, such as HOTTIP, EGFR‐AS1, FAL1, and LINC01503 .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 For example, LINC00336 was reported to facilitate lung cancer progression via sponging miR-6,852 9 ; LncRNA SNHG6 directly bound to miR-26a/b and miR-214 to promote the growth and metastasis of colorectal cancer 10 ; LncRNA MEG3 was proposed to suppress migration and promote apoptosis of oral squamous cell carcinoma cells by effectively sponging miR-548d-3p. 11 Likewise, several lncRNAs have also been identified to be involved in ESCC tumorigenesis, such as HOTTIP, 12 EGFR-AS1, 13 FAL1, 14 and LINC01503. 15 Thus, although a small fraction of lncRNAs in cancer have been well delineated, the roles of many members in this class are still unknown, which needs to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%